BRAND IMAGE, ONLINE CUSTOMER RATING DAN ONLINE CUSTOMER REVIEW TERHADAP KEPERCAYAAN KONSUMEN PADA TOKOPEDIA - Ni Nyoman Febby Cahyani; Ni Wayan Sitiari; I. A. Cynthia Saisaria Mandasari (Fakultas Ekonomi Universitas Warmadewa, 2024)
This research has the title “The Influence of Brand Image, Online Costumer Ratings and Online Costumer Review on Costumer Trust in The Tokopedia Marketplace in Belega Village, Blahbatuh District”. The aim of this research is to analyze the influence of brand image, online costumer reviews simultaneously and partially on consumer trust in the Tokopedia marketplace in Belega Village, Blahbatuh District. The population in this research is the Tokopedia consumer market in Belega Village, Blahbatuh District which cannot be identified. The number of samples in this research was 85 consumers. The sampling technique is purposive random sampling. Tha analytical tools used are validity and reliability tests, multiple linear regression analysis, simultaneous tests (F-test), and invidivual parameter significance tests (t-test). The research results shows that the variables brand image, online customer rating and online customer review have a positive and significant effect simultaneously and partially on consumer trust in Tokopedia marketplace in Belega Village, Blahbatuh District.